PENGARUH PIJAT TUI NA TERHADAP PERILAKU MAKAN PADA BALITA DI WILAYAH KERJA PUSKESMAS TALISE KOTA PALU - Mutmaina (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2023)
fulfillment of nutrition. At the age of toddlers often children experience bad behavior. One of the problems that are often experienced is the difficulty of feeding children which directly interferes with the child's growth and development. Non-pharmacological efforts that can be done include herbal drinks, massage, acupressure and acupuncture. The purpose of this study was the effect of Tui Na massage on eating behavior in toddlers in the Talise Community Health Center in Palu City in 2022 This research design is a pre-experimental study with a one group pretest- posttest design approach. The population is all children under five in the Talise Health Center in Palu City in 2022, with a purposive sampling method obtained a sample of 20 respondents. The independent variable studied was the provision of Tui Na massage, while the dependent variable was eating behavior. The results were analyzed using a paired sample T test. The results of the study prior to the Tui Na massage, most of the respondents had good eating behavior (80%) and a small proportion of respondents had good eating behavior (20%). After the Tui Na massage, most of the respondents had good eating behavior (65%) and a small proportion of respondents had good eating behavior (35%). The results of data analysis using the paired sample T test showed that the p-value = 0.000 is smaller than the critical value = 0.05, because the p-value < then H0 is rejected and H1 is accepted, which means there is an effect of Tui Na massage on eating behavior in children. toddlers in the Talise Health Center in Palu City in 2022 Giving Tui Na massage that has been done is able to launch the blood circulation system so that it can increase the supply of oxygen and the flow of nutrients in the body's cells, especially in the digestive organs so that the digestive organs are able to work optimally. Optimal work of the digestive organs will make toddlers feel hungry quickly because food absorption is better, so toddlers feel hungry more often and are able to eat well.